2018
DOI: 10.11648/j.ajpst.20180401.13
|View full text |Cite
|
Sign up to set email alerts
|

Adhesives and Adhesion Technologies: A Critical Review

Abstract: The article critically reviews about adhesives and their various adhesion phenomenons along with their categorization and functions. Benefit and drawbacks of adhesives joining was explained. Requirements for excellent bonding which includes, appropriate selection of adhesive, superior design for joining, surface cleansing, wetting were defined. The review clearly indicates the various theories involved in adhesion are namely mechanical interlocking, electrostatic, diffusion, wetting, chemical bonding, and weak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…Plasma treatments offer an alternative method to prepare surfaces of carbon fiber composites for bonding and possess several advantages over traditional mechanical and chemical approaches. 25,26 Atmospheric and low-pressure plasma discharges produce high-energy ions and reactive radicals that interact with composites to change the micrometer-scale morphology and chemical functions of the surface with minimal impact on the integrity of the bulk structure. 26,27 These plasma treatments may obviate the use of organic solvents, reduce ergonomic impact on operators, and may improve success and reproducibility of adhesion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma treatments offer an alternative method to prepare surfaces of carbon fiber composites for bonding and possess several advantages over traditional mechanical and chemical approaches. 25,26 Atmospheric and low-pressure plasma discharges produce high-energy ions and reactive radicals that interact with composites to change the micrometer-scale morphology and chemical functions of the surface with minimal impact on the integrity of the bulk structure. 26,27 These plasma treatments may obviate the use of organic solvents, reduce ergonomic impact on operators, and may improve success and reproducibility of adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma treatments offer an alternative method to prepare surfaces of carbon fiber composites for bonding and possess several advantages over traditional mechanical and chemical approaches. , Atmospheric and low-pressure plasma discharges produce high-energy ions and reactive radicals that interact with composites to change the micrometer-scale morphology and chemical functions of the surface with minimal impact on the integrity of the bulk structure. , These plasma treatments may obviate the use of organic solvents, reduce ergonomic impact on operators, and may improve success and reproducibility of adhesion. Seminal work in this area demonstrated that an atmospheric-pressure O 2 discharge introduces multiple forms of oxygenated functions to the surface of carbon fiber composites (manufactured from Nelcote E765 epoxy and AS4 PAN-based carbon fibers), and the interfacial adhesion strength correlated with the coverage of carboxylic acid surface functions, which were determined by lap shear tests and X-ray photoelectron spectroscopy (XPS), respectively. , The authors attributed these changes to chemical bonds formed between these carboxylic acid groups and epoxide functions within the adhesive.…”
Section: Introductionmentioning
confidence: 99%
“…A adesão é um fenômeno como objetivo de unir componentes, sendo de grande interesse em todas as áreas do conhecimento, inclusive a biomédica, que contribui para conferir resistência, biomateriais com adesividade apropriadas para a aplicação desejada, substituindo técnicas tradicionais de fixação mecânica, melhorando o processo de cicatrização e diminuição nas trocas. Curativos com excelente aderência à base da lesão de pele ou em determinados tipos de feridas possibilita a não contaminação externa e perda de líquidos, que favorecem o processo de cicatrização e promove a redução da necessidade de substituição dos curativos (Bharti, 2018;Pereira et al, 2019).…”
Section: Introductionunclassified